PENGARUH PENAMBAHAN EMULSIFIER PADA BERBAGAI LEVEL TERHADAP KUALITAS PRODUK HOME MADE YOGURT YANG MENGGUNAKAN YOGURT PLAIN SEBAGAI STARTER - Satria, Heppi Kurniadi (Universitas Kanjuruhan Malang, 2013)
Research carried out in an integrated laboratory Kanjuruhan University of Malang , on 22-23 December 2013 . The purpose of this study was conducted to determine the effect of adding an emulsifier to the various levels of product quality home made yogurt using plain yogurt as a starter . The material used in this study were fresh cows milk , skim milk powder , plain yogurt as a starter , emulsifier Carboxymethylcellulose. The method used was a laboratory experiment using a completely randomized design ( CRD ) with 3 treatments and each repeated 3 times . The treatment used is the level of emulsifier 3 g , 6 g , 9 g of ½ liter of milk with a 24- hour incubation period . Observed variables include pH , protein content , organoleptic quality ( color , texture , aroma and flavor ) yogurt. Based on the results of this study concluded that the addition of an emulsifier at different levels of effect on the crude protein content of home made yogurt products that use plain yogurt as a starter . The highest level P>0,05 on the use of emulsifiers 9 g of 4.27 % . The addition of emulsifiers at various levels had no effect on pH and organoleptic quality of the products that use home made yogurt plain yogurt as a starter . Key word: yogurt, emulsifier, yogurt plain, home made, starter